Digital leadership, learning agility, and employee performance in Indonesia’s automotive industry: A view from Islamic economic perspectives - Gunawan, Ahmad; Sucipto, Imam; Heri Kusumah, Dadang; Saddaf, Nabila; Manan, Irma Rohmatul (Journal of Islamic Economics Lariba, 2026)
IntroductionIndonesia’s automotive industry is facing rapid digital transformation, intensifying global competition, and increasing pressure to improve quality, productivity, and adaptability. These challenges require organizations to strengthen digital leadership, employee competence, organizational commitment, and learning agility. However, the mechanisms through which these factors improve employee performance remain insufficiently explained, especially when viewed from an Islamic economics perspective.ObjectivesThis study examines the influence of digital leadership, competence, and motivation on employee performance in Indonesia’s automotive industry. It also analyzes the mediating roles of organizational commitment and learning agility and interprets the findings through Islamic economics values, including amanah, ihsan, adl, maslahah, and falah.MethodThis study used a quantitative approach with a survey method. Data were collected from 335 managers, supervisors, and employees in Indonesia’s automotive industry who had experience with digital transformation or technology-based work processes. The research model was tested using Partial Least Squares Structural Equation Modeling. Validity and reliability were assessed through factor loading, composite reliability, and average variance extracted, while direct and indirect relationships were examined through path analysis and bootstrapping.ResultsThe results show that digital leadership has a significant direct effect on employee performance but does not significantly influence learning agility and only marginally affects organizational commitment. Motivation does not significantly affect performance, organizational commitment, or learning agility. Competence has a strong significant effect on organizational commitment, while organizational commitment significantly improves learning agility. Learning agility is the strongest direct predictor of employee performance. The most important indirect pathway is competence → organizational commitment → learning agility → performance.ImplicationsThis study indicates that improving employee performance in the automotive industry requires more than digital leadership and motivation. Organizations should strengthen employee competence, build organizational commitment, and develop learning agility through fair, ethical, and welfare-oriented human resource practices.Originality/NoveltyThis study contributes an integrated model of digital leadership, competence, organizational commitment, learning agility, and performance in the automotive industry, enriched by an Islamic economics perspective on ethical and sustainable human resource development.